THE EFFECT OF VARIOUS RATES OF COW MANURE APPLICATION ON GROWTH AND YIELD OF MUSTARD (BRASSICA JUNCEA L.) - Nur Humairoh Arzad; Yohanis Tambing; Bahrudin Bahrudin (AGROLAND: The Agricultural Sciences Journal, 2017)
The research was conducted in the village of Sidera, Subdistrict of Sigi Biromaru, District of Sigi, in May to June 2016. The research aims to find out the effect of various rates of cow manure on growth and yield of mustard.this research was arranged  in a randomized block design (RBD) which consist of 5 rates ofcow manure are: 10 t ha-1, 15 t ha-1, 20 t ha-1, 25 tha-1 and 30 t ha-1 , each treatment was repeated three times to obtain 15 units experiment. The results of this research showed that the application of cow manure significantly affected on growth and yield of mustard plants (plant height, number of leaves, fresh weight and dry weight of plant) and best rate of manure to mustard (Brassica juncea L.) can be achieved at the dose of 25 t ha-1.